Efeito do cálcio e fósforo disponível na dieta sobre o desempenho produtivo, qualidade óssea e da casca de ovos de galinhas poedeiras por meio de meta-análises - Diego Pereira Vaz (2018)
Two studies were conducted to evaluate the effects of calcium and available phosphorus levels in the diet on feed intake, egg production, egg weight, egg mass, conversion feed ratio, eggshell percentage, eggshell thickness, specific gravity and ash percentage of the tibia of laying hens using a meta-analytic approach. Mixed models were used to evaluate the linear and quadratic effects of calcium and available phosphorus levels on the response. In the metaanalysis that evaluated the effect of calcium the database consisted of 37 trials and 22 scientific articles published from 1993 to 2015. Feed intake decreased linearly and the percentage of ash in the tibia increased linearly as a function of the increase of calcium levels in the diet, estimates of linear calcium coefficients were different from zero with P values equal to 0.0007 and 0.0215, respectively. Egg production (P = 0.0266), egg mass (P = 0.0143), feed conversion (P = 0.0142), egg shell percentage (P 0.0001), shell thickness P = .0385) and specific gravity (P 0.0001) were influenced in a quadratic form by the increment of calcium levels of the diet. The meta-analysis evaluating the effect of phosphorus available the database consisted of 30 trials, extracted from a dissertation and 17 articles published from 1993 to 2017. The performance variables were influenced by the increase in dietary phosphorus levels in a linear (ie, egg weight, P = 0.0308) and quadratic form (ie, feed intake, P = 0.0040, egg production; P = 0.0007 and egg mass, P = 0.0004), since the estimates of the linear and quadratic coefficients of the available phosphorus were different from zero. However, the bone quality and egg shell variables of laying hens were not influenced by the levels of available phosphorus. Diets containing calcium levels of 39.22 and 44.45 g/kg promote the maximum performance response and eggshell quality in laying hens, respectively. As well as, diets containing the Pd level of 3.82 g/kg promote maximum performance response without compromising eggshell quality in laying hens.